Nosocomial infection in a tertiary military hospital in Dhaka (Bangladesh Medical Journal Khulna, 2018)
Background: Microbial agents in the hospital environment and other patients increase the morbidity and mortality of the hospitalized patients and cause increase in cost of care, wastage of scarce medical resources prolonged hospitalization and render non availability of scarce hospital beds to the needy.Objective: To find out the prevalence of Nosocomial Infection (NI), its risk factors and pattern of organisms.Method: This descriptive cross sectional study was conducted among the surgical patients of all age and sex at Combined Military Hospital, Dhaka. The study was conducted from 5 April 2014 to 12 April 2015.Results: A total of 360 respondents were available in different surgical wards during data collection period and 30 respondents developed nosocomial infection, thus the prevalence rate was 8.33%. The mean age of the respondents was 36.89 years with standard deviation of (±) 14.54 years. Among the nosocomial infection cases, 53.33% were surgical site infections and 50% were caused by Escherichia coli. The study found that frequency of nosocomial infection was more common among those who required assistance for most activities (40%), who had visitors more than 3 per day (81.3%), who had underlying illness like diabetes mellitus (25%), who had invasive devices (9.5%), who were admitted in ICU (12.9%), who received immunosuppressive therapy (23.5%), who had immunosuppressive conditions (28.1%), who had emergency operation (34.8%), and who had undergone general surgery (19.0%). Findings suggest that association between nosocomial infection and number of visitors, admission in ICU, immunosuppressive conditions, use of immunosuppressive therapy, use of invasive devices, and different functional state of patients were statistically significant (p